Protein Quantity and Quality of Safflower Seed Improved by NP Fertilizer and Rhizobacteria (Azospirillum and Azotobacter spp.) - Nosheen, Asia; Bano, Asghari; Yasmin, Humaira; Keyani, Rumana; Habib, Rabia; Shah, Syed T. A.; Naz, Rabia (Frontiers in Plant Science, 2016)
Protein is an essential part of human diet. The aim of present study was to improve the protein quality of safflower seed by the application of plant growth promoting rhizobacteria (PGPR) in combination with conventional nitrogen and phosphate (NP) fertilizers. The seeds of two safflower cultivar Thori and Saif-32, were inoculated with Azospirillum and Azotobacter and grown under field conditions. Protein content and quality was assessed by crude protein, amino acid analysis and SDS-PAGE. Seed crude protein and amino acids (metheonine, phenylanine and glutamic acid) showed significant improvement (55%–1250%) by Azotobacter supplemented with quarter dose of fertilizers (BTQ) at P≤0.05. Additional protein bands were induced in Thori and Saif-32 by BTQ and BTH (Azotobacter supplemented with half dose of fertilizers) respectively. The Azospirillum in combination with half dose of fertilizers (SPH) and BTQ enhanced the indole acetic acid (90%) and gibberellic acid (23%–27%) contents in safflower leaf. Taken together, these data suggest that Azospirillum and Azotobacter along with significantly reduced (up to 75%) use of NP fertilizers improved the quality and quantity of safflower seed protein.